Identification of Melia azedarach and Eucalyptus camaldulensis as natural hosts and reservoirs of phytoplasmas in India. Issue 1 (22nd January 2022) - Mitra, Surabhi; Ravi, Manish; Rao, Govind Pratap
Abstract: Witches' broom, leaf yellowing and little leaf symptoms were recorded on Melia azedarach in Pune district of Maharashtra and Dhanha, West Champaran district of Bihar. Little leaf and leaf yellowing symptoms also were recorded on Eucalyptus camaldulensis in Bhiwani district of Haryana. Symptomatic and asymptomatic leaf samples were collected from roadside trees for DNA extraction and PCR assay with phytoplasma‐specific primer pairs of 16S rRNA and secA genes. Amplicons of 1.25 kb and 840 bp were consistently obtained from all symptomatic samples of both the tree species using the phytoplasma‐specific primer pairs. Pairwise sequence analysis of 16S rRNA and secA gene sequences and phylogenetic analysis revealed that the phytoplasma strains associated with M . azedarach belonged to 16SrI‐B and 16SrVI‐D subgroups and those associated with E . camaldulensis were from the 16SrII‐D subgroup. This is the first report of an association of a ' Candidatus Phytoplasma trifolii'‐related strain (16SrVI‐D subgroup) with M . azedarach globally and a ' Ca . P. australasia'‐related strain with E . camaldulensis in India.